Parent-Child and Center-Edge Metaphors: A Theological Engagement with the Social Imaginary of "One Country, Two Systems" - Kung, Lap Yan (Political theology, 2019)
This paper examines how the social imaginary of "one country, two systems" is built on the traditional Chinese conception of a parent-child relation. However, the parent-child metaphor is no longer shared by the new generation in Hong Kong. The change of the sociopolitical environment in Hong Kong in the Post-Umbrella Movement demands a new social imaginary for understanding "one country, two systems." This paper argues that the metaphor of reconciliation proposed by the churches and supported by the Hong Kong government fails to respond to the experience of the Hong Kongese, recommending instead a metaphor of center-edge in dialogue with insights from liberation theologies. In terms of geography, politics, and culture, living on the edge helps the Hong Kongese to articulate their experience in a situation of decreasing protection of human rights in Hong Kong.